2021
DOI: 10.1113/jp281712
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for kisspeptin in metabolism

Abstract: Kisspeptin, a neuropeptide hormone, has been firmly established as a key regulator of the hypothalamic-pituitary-gonadal axis and mammalian reproductive behaviour. In recent years, a growing body of evidence has emerged suggesting a role for kisspeptin in regulating metabolic processes. This data suggest that kisspeptin exerts its metabolic effects indirectly via Chioma Izzi-Engbeaya (MBBS PhD MRCP) is an Imperial-BRC Research Fellow at Imperial College London and a Consultant Endocrinologist at Imperial Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Kisspeptin neurons in the arcuate nucleus are involved in the negative feedback regulation of the HPG axis and express androgen receptors [ 32 , 33 ]. Kisspeptin has been shown to enhance the expression of orexigenic NPY and attenuate the expression of anorexigenic POMC [ 32 , 34 , 35 , 36 ], and the glucosensitive NPY neurons are known to connect reciprocally with orexin A neurons [ 37 , 38 , 39 ]. These findings suggest that the enhanced responses of feeding and orexin A neuron activity to reduced glucose availability in orchiectomized rats are mediated by increased NPY, induced by a lower level of androgens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kisspeptin neurons in the arcuate nucleus are involved in the negative feedback regulation of the HPG axis and express androgen receptors [ 32 , 33 ]. Kisspeptin has been shown to enhance the expression of orexigenic NPY and attenuate the expression of anorexigenic POMC [ 32 , 34 , 35 , 36 ], and the glucosensitive NPY neurons are known to connect reciprocally with orexin A neurons [ 37 , 38 , 39 ]. These findings suggest that the enhanced responses of feeding and orexin A neuron activity to reduced glucose availability in orchiectomized rats are mediated by increased NPY, induced by a lower level of androgens.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced c-Fos expression in the dorsomedial Arc by orchiectomy in the present study suggests a possibility that reduced androgen enhances the NPY neurons by stimulating the kisspeptin neurons. However, kisspeptin has also been reported to excite POMC neurons and inhibit NPY neurons [ 32 , 34 , 40 ], and intracerebroventricular kisspeptin reduces food intake [ 41 ], suggesting that kisspeptin has anorexigenic properties. In contrast, some studies reported that an intracerebroventricular injection of kisspeptin had no effect on food intake [ 32 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also suggest that KP neurons in ARC nuclei regulate lactation [ 171 ], appetite and growth hormone release [ 172 ]. Findings in whole body knockout models of KPR (KPR KO ) suggest that KP-signaling plays an important role in energy expenditure, food intake and body weight gain and this is sexually dimorphic [ 173 , 174 ]. KPR KO female mice gained body weight and developed impaired glucose tolerance, but the KPR KO male mice suffered loss of body weight due to a suppression of feeding [ 174 , 175 ].…”
Section: Physiological Functions Of Hypothalamic Kisspeptinsmentioning
confidence: 99%
“…Data from in KPR KO mice suggest that KP-signaling may impact energy expenditure, food intake and body weight in a sexually dimorphic manner [ 173 , 174 ]. The metabolic and diabetic phenotypes in KPR KO mice could be due to reduced pancreatic β-cell function and the absence of peripheral KP-signaling [ 202 , 203 ].…”
Section: The Biology Of Extrahypothalamic Kisspeptinsmentioning
confidence: 99%
See 1 more Smart Citation